Pengaruh Kepemimpinan Transformasional dan Kepemimpinan Pemberdayaan terhadap Kepuasan Kerja dan Kinerja Karyawan di Era Digital - Maidiana Astuti Handayani; Zaleha Trihandayani; Eni Cahyani (Universitas Muhammadiyah Palembang, 2026)
Purpose – This study aims to analyze the effect of transformational leadership and empowering leadership on job satisfaction and employee performance in organizations operating in the digital era. Design/methodology – This research uses a quantitative approach with an explanatory survey method to examine the empirical relationship among variables. The population consists of permanent employees working in service and education organizations that actively implement work digitalization. A total of 109 respondents were selected using purposive sampling based on tenure and direct involvement in the organization’s digital transformation process. Data were analyzed using quantitative techniques to test direct and indirect effects through job satisfaction as a mediating variable. Findings – The results show that both transformational leadership and empowering leadership have a positive and significant effect on job satisfaction and employee performance, directly and indirectly through job satisfaction. Leaders who inspire, serve as role models, and foster self-confidence among subordinates create a conducive work climate, enhancing motivation and productivity. The findings highlight that the combination of transformational and empowering leadership styles serves as an effective strategy to face modern leadership challenges, especially during digital transformation processes in Indonesian organizations.